2012
DOI: 10.1038/srep00393
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed, Self-organized Organic Single Crystal Arrays with Controlled Crystal Orientation

Abstract: A facile solution process for the fabrication of organic single crystal semiconductor devices which meets the demand for low-cost and large-area fabrication of high performance electronic devices is demonstrated. In this paper, we develop a bottom-up method which enables direct formation of organic semiconductor single crystals at selected locations with desired orientations. Here oriented growth of one-dimensional organic crystals is achieved by using self-assembly of organic molecules as the driving force to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 43 publications
(67 reference statements)
2
89
1
Order By: Relevance
“…S7). In comparison, other patterning methods used to create patterned OSCs for isolated OTFTs have shown relative variances ranging from 20% to 84% (9,15,17,22,31,32,35,42,(48)(49)(50)(51)(52)(53)(54). For example, Li et al (15) have shown that using a PMMA:C8BTBT blend on a solution wetting pattern can deposit crystal plates that have a mobility relative variance of >40%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7). In comparison, other patterning methods used to create patterned OSCs for isolated OTFTs have shown relative variances ranging from 20% to 84% (9,15,17,22,31,32,35,42,(48)(49)(50)(51)(52)(53)(54). For example, Li et al (15) have shown that using a PMMA:C8BTBT blend on a solution wetting pattern can deposit crystal plates that have a mobility relative variance of >40%.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, alignment using inkjet printing is restricted by the registration capability of the instrument, whereas the size of each OTFT is limited by the droplet size attainable (22,31). Another potential issue with these methods is the variance in electrical characteristics of TFTs due to the difficulty in obtaining uniform crystal growth on isolated TFTs over large areas (9,15,21,27,28,(31)(32)(33)(34)(35). Even single crystalline domains of patterned TFTs may have large variability in electrical characteristics as a result of random orientation and size variance.…”
mentioning
confidence: 99%
“…This strategy has been demonstrated by limiting the growth area 15 using line patterns of fluorinated polymers or self-assembled monolayers. 30 The bounded crystals can then reorient during growth along the patterned direction. In this approach, the alignment of stencil mask apertures to the patterned areas remains a technical challenge that is left to further work.…”
mentioning
confidence: 99%
“…Besides, without PMMA, the crystals were not grown in the trenches, confirming the role of PMMA to absorb the chloroform, enabling C8-BTBT molecules to reorient easily for crystallization. An organic single-crystal array with single-crystal orientation over a wide area was thus achieved by using PASVA [456], with the evidence that the crystals were formed only in the trenches and they were uniformly similar, indicating good control of both the crystal positions and orientations. The X-ray diffraction (XRD) analysis confirmed that the C8-BTBT molecules were stacked in the same direction [456].…”
Section: Special Os Crystalsmentioning
confidence: 99%
“…This method was carried out on a patterned substrate, limiting the growth direction of the crystals and allowing the fine control of the crystal location and orientation over a wide area. In a subsequent experiment [457], an SiO 2 -coated Si substrate was patterned into wetting/dewetting regions using OS solution [456][457][458][459] as mentioned earlier. The wetting regions were defined by standard photolithography followed by Cytop™ spin-coating and annealing at 90°C.…”
Section: Special Os Crystalsmentioning
confidence: 99%